Ramesh and Gargi (A) - Vohra, Neharika; Pattnaik, Snigdha (London : SAGE Publications Ltd, 2017)
Ramesh Sharma, the head of Learning and Development (L&D) at Chrysalis Pharmaceuticals, had enjoyed his lunch meeting with the Human Resources (HR) head of a large retail company, but he drove back to his office with mixed feelings. He was both happy and unhappy at the same time; happy because he had options to fall back on if he decided to quit Chrysalis Pharmaceuticals, and unhappy at the thought of leaving his dream job. Chrysalis Pharmaceuticals, a large multinational drug manufacturer, had set up shop in India in 2009 and had its corporate headquarters in Chennai, the capital of the southern state of Tamil Nadu. Ramesh had been handpicked by its CEO, Raman Murthy, and vice president of HR, Kamla Saxena, to head the L&D department. Kamla had been Chrysaliss third employee and Ramesh, its fifth. Chrysalis had grown from strength to strength in the last four years, had set up manufacturing plants in four cities in India and currently employed 1,200 people. During this period, Ramesh had partnered with Kamla not only on the onboarding, training and career planning of new hires but also on putting in place sound HR policies and practices. However, the last six months had been strange and discomforting, and he was unsure of the messages he was receiving from Kamla.
Originally published: Vohra, N., & Pattnaik, S. (2014). Ramesh and Gargi (A). OB0216(A). Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sharma, Ramesh; Saxena, Kamla; Chrysalis Pharmaceuticals; Pharmaceutical industry -- India -- Case studies; Pharmaceutical policy -- India -- Case studies